If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w = -6w + -7 Reorder the terms: -5w = -7 + -6w Solving -5w = -7 + -6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6w' to each side of the equation. -5w + 6w = -7 + -6w + 6w Combine like terms: -5w + 6w = 1w 1w = -7 + -6w + 6w Combine like terms: -6w + 6w = 0 1w = -7 + 0 1w = -7 Divide each side by '1'. w = -7 Simplifying w = -7
| -3t-6-2t=-6-5t | | 15x-2-6x= | | 5ln(x+1)=30 | | 2a-3a=20 | | (3X)3=24 | | (y+4)(3y-2)=-y-14 | | -2(14q-20)-4=-4(7q-9) | | 0.8-z=2.1 | | 15x-2-6x=45 | | (2x-3)+(7x+21)=90 | | 13x-29=155 | | -9.39-3.4d=-1.1d | | x^2-3xy+3y^2+6y=7 | | 4x+4z-2y=-1 | | 7(X-6)= | | b-7=12# | | (3X)9=24 | | (3X)9=25 | | 0=-3x^2+4x | | X+2015=Y | | 4m+5=48 | | (2x-3)=90 | | P-25=-53 | | 6x+7x-5x=-48 | | 6y=5y-8.6 | | (2x-3)=180 | | x^3+(2-i)x^2+(-4-3i)x+(1+i)=0 | | 6g=18# | | -2(y+1)=-4y+10 | | [2x-1]=3x | | 36=(x-1)2+(y-5)2 | | 7y-c=b |